2019
DOI: 10.1021/acsami.9b08392
|View full text |Cite
|
Sign up to set email alerts
|

Spark Plasma Sintered Bulk Nanocomposites of Bi2Te2.7Se0.3 Nanoplates Incorporated Ni Nanoparticles with Enhanced Thermoelectric Performance

Abstract: Bi2Te3-based compounds are important near room temperature thermoelectric materials with commercial applications in thermoelectric modules. However, new routes leading to improved thermoelectric performance are highly desirable. Incorporation of superparamagnetic nanoparticles was recently proposed as a means to promote the thermoelectric properties of materials, but its feasibility has rarely been examined in mainstream thermoelectric materials. In this study, high quality single-crystalline Bi2Te2.7Se0.3 nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 37 publications
2
22
0
1
Order By: Relevance
“…Further optimization of carrier concentration and additional methods for decreasing lattice thermal conductivity would improve the thermoelectric property obviously. The average zT values obtained in this work are displayed in Figure d, together with other reported n-type Bi 2 Te 3 -based materials. , The average zT in both directions in this work approached to 1.0, which is competitive and promising for achieving a high-energy conversion efficiency.…”
Section: Results and Discussionsupporting
confidence: 60%
“…Further optimization of carrier concentration and additional methods for decreasing lattice thermal conductivity would improve the thermoelectric property obviously. The average zT values obtained in this work are displayed in Figure d, together with other reported n-type Bi 2 Te 3 -based materials. , The average zT in both directions in this work approached to 1.0, which is competitive and promising for achieving a high-energy conversion efficiency.…”
Section: Results and Discussionsupporting
confidence: 60%
“…The κ tot was calculated according to κ tot = DC P d using the thermal diffusion coefficient (D) measured by the laser flash method (LFA 457, Netzsch, Germany). The measurement uncertainties for σ, S and D are approximately 5%, and the measurements were conducted along the direction perpendicular to the SPS compression because the TE performance along this direction is always superior to that along the parallel direction for polycrystalline (Bi,Sb) 2 Te 3 , as has been extensively confirmed in previous studies [37][38][39]. The mass density (d) was obtained by the Archimedes method.…”
Section: Methodsmentioning
confidence: 76%
“…Past research has indicated superior TE performance along the direction perpendicular to the SPS compression compared to the parallel direction for Bi 2 Te 3 -based materials. ,, Therefore, the TE properties of the final commercial p -type (Bi,Sb) 2 Te 3 scraps + SiC samples were conducted along the same direction. The results are presented in Figures and .…”
Section: Results and Discussionmentioning
confidence: 99%